2011
DOI: 10.1371/journal.pone.0026645
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Evolution of the Mitochondrial Genome in Chalcidoid Wasps (Hymenoptera: Chalcidoidea) Driven by Parasitic Lifestyles

Abstract: Among the Chalcidoids, hymenopteran parasitic wasps that have diversified lifestyles, a partial mitochondrial genome has been reported only from Nasonia. This genome had many unusual features, especially a dramatic reorganization and a high rate of evolution. Comparisons based on more mitochondrial genomic data from the same superfamily were required to reveal weather these unusual features are peculiar to Nasonia or not. In the present study, we sequenced the nearly complete mitochondrial genomes from the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 31 publications
3
44
0
Order By: Relevance
“…The presence of greater nucleotide sequence divergence indicates a purifying selection in seven genes (cox1, cox2, cox3, cob, atp6, nad1 and nad3), while the greater amino acid substitution suggests either positive or relaxed selection in remaining six genes (Fig. 3) (Oliveira et al, 2008;Xiao et al, 2011). The similar pattern is also observed in d N /d S ratios with atp8, nad6 and nad2 displaying the most variable substitution rates (Fig.…”
Section: Protein-coding Genes and Codon Usagementioning
confidence: 55%
See 1 more Smart Citation
“…The presence of greater nucleotide sequence divergence indicates a purifying selection in seven genes (cox1, cox2, cox3, cob, atp6, nad1 and nad3), while the greater amino acid substitution suggests either positive or relaxed selection in remaining six genes (Fig. 3) (Oliveira et al, 2008;Xiao et al, 2011). The similar pattern is also observed in d N /d S ratios with atp8, nad6 and nad2 displaying the most variable substitution rates (Fig.…”
Section: Protein-coding Genes and Codon Usagementioning
confidence: 55%
“…The abnormal initiation codons have been accepted as canonical mitochondrial start codons for invertebrate mitogenomes and usage of alternative codons have been suggested to function in minimizing intergenic spacer and avoiding overlaps between adjacent genes (Bae et al, 2004;Sheffield et al, 2008;Wei et al, 2010a,b). Four genes, (cox1 and nad6 in all three species, nad2 in C. cinctus and C. sareptanus and nad4 in C. sareptanus) have truncated termination codons T − or TA −, as commonly seen in invertebrate mitogenomes, and their products are probably completed posttranscriptionally by the polyadenylation of mature mRNA (Ojala et al, 1980;Oliveira et al, 2008;Xiao et al, 2011).…”
Section: Protein-coding Genes and Codon Usagementioning
confidence: 92%
“…Only a few mitochondrial genomes have been reported in this group (Chen et al, 2018; Nedoluzhko et al, 2016; Oliveira et al, 2008; Su et al, 2016; Xiao et al, 2011; Xiao et al, 2012; Yang et al, 2018; Zhu et al, 2018). Mitochondrial control regions were reported difficult to be amplified in Chalcidoidea for unknown reasons (Oliveira et al, 2008; Xiao et al, 2011; Xiao et al, 2012; Zhu et al, 2018). In Nasonia , several PCR conditions using all possible combinations failed in joining two mitochondrial coding fragments (Oliveira et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although sampling is limited, studies revealed rapid evolution of mitochondrial genomes in Chalcidoidea. Dramatic gene order rearrangement and extremely high substitution rates are observed (Chen et al., 2018; Oliveira et al, 2008; Xiao et al, 2011; Xiao et al, 2012; Yang et al, 2018). A striking example is that intraspecific synonymous substitution rates in mitochondria between Wolbachia infected and uninfected fig wasp Ceratosolen solmsi (Agaonidae) is even higher than the mitochondrial interspecific synonymous substitution rates among Drosophila species (Xiao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the model often discards evolutionary scenarios of genes that evolve with rapid rates of gene duplication and loss events, and several of such genes are biologically appealing like the MHC gene family (e.g., Slade et al, 1994), the olfactory receptor genes (e.g., Xiao et al, 2011), and the rhodopsin genes (e.g., Sugawara et al, 2002). To make matters worse, the parsimony model does not consider evolutionary time that is usually represented as edge lengths in the species tree, and a gene duplication may occur more likely on an edge that represents 100 million years than on an edge representing a fraction of this time.…”
Section: Related Workmentioning
confidence: 99%